Development and Validation of Multiplex Assays for Lupus Nephritis Activity Biomarkers - Ellen M. Cody; Alyssa Sproles; James Rose; Bin Huang; Prasad Devarajan; Hermine I. Brunner; Sherry Thornton (Kidney International Reports, 2025)
Introduction: We aimed to develop multiplex (MLP) assays of 6 biomarkers, namely adiponectin, neutrophil gelatinase-associated lipocalin (NGAL), monocyte chemoattractant protein-1 (MCP-1), kidney injury molecule-1 (KIM-1), ceruloplasmin, and hemopexin used in the Renal Activity Index for Lupus (RAIL) and establish MLP assays using the Milliplex MLP and the electrochemiluminescence Mesoscale Discovery (MSD) technology, to compare with the gold standard of established single immunoassays. Methods: A total of 104 banked urine samples from the CCHMC Lupus Cohort were used. RAIL biomarker concentrations were assayed using established individual immunoassays, and concentrations were compared with MLP reagents using both the MSD and MLP platforms. MLP assay development involved assessment of biomarker concentrations in 40 individual urine samples, followed by evaluation of optimal sample dilution using 14 additional samples on each platform. Then 50 samples were assayed in duplicate under optimized MLP conditions, and biomarker concentration compared with those using single assays. After correcting for urine creatinine, RAIL scores of the samples were determined and compared between testing platforms (single immunoassays, MLP). Results: Our results indicate that a 1:25 urine dilution was optimal when using the MLP platforms. Biomarker concentrations by single immunoassays correlated with those on the Milliplex platform strongly for KIM-1, MCP-1, and NGAL (r = 0.726–0.86, P < 0.0001), moderately for adiponectin (r = 0.629, P < 0.0001) and weakly for ceruloplasmin (r = 0.367, P = 0.009). Using the MSD platform, comparatively lower correlations with those by single immunoassay were observed (NGAL: r = 0.516, P = 0.0001; adiponectin and hemopexin: r ≤ 0.29, P = 0.042; ceruloplasmin, KIM-1, and MCP-1: all r < 0.2). Conclusion: Milliplex technology is suitable to measure RAIL biomarker concentrations in urine samples diluted 1:25.